KISARAN INANG Corynespora cassiicola (Berk. & Curt) Wei PADA TANAMAN DI SEKITAR PERTANAMAN KARET (Hevea brassiliensis Muell) - Suryani Sajar (Talenta Publisher, 2017)
Leaf fall disease caused by Corynespora cassiicola is the most important disease in a rubber plantation. Thedisruption will decrease the productivity, delaying on grafting in a nursery and hard attack will flaw the seed,stunted and even dead. Curative prevention on old crop need huge expenses with uncertain result, hence it isnecessary to understand the host range of C. cassiicola completed with its cultural characteristics to utilizedin disease preventions such as intercropping and mixed cropping recommendation for weed control action.This study aims to obtain plants that are host of C. cassiicola. This research showed that isolate of C. cassiicolafrom clone GT1 of rubber infected 12 plants from 16 tested plants in various incubation periods which were:cucumber, soybean, alamanda, papaya, cassava, babadotan, sweet potato, tapak dara, peanuts, asystasia,mucuna, and RRIM 600. Pathogenicity examination showed 5 resistence degree, which were: resistant(babadotan, lulangan weed, sweet potato, mucuna, lantana, asystasia, spinach torm and sembung rambat) ;slightly resistant (rubber, peanuts, alamanda and tapak dara) ; moderate (soybean and papaya) ; slightlysusceptible (cassava) and susceptible (cucumber).